Incorporation of Platinum onto Zeolite KL for aromatisation reactions - M'kombe,Chamu Mark (Department of Chemical Engineering, 2016)
The main objectives of the work presented in this thesis were two fold - i) to determine the effect of varying various parameters on the platinum dispersion and ii) to determine the conditions that would yield the highest platinum dispersion on the zeolite KL. Loading of platinum onto the zeolite KL was mainly via liquid state ion exchange. Loading via impregnation and solid state ion exchange were also briefly investigated in order to compare these techniques with liquid ion exchange. After loading the platinum onto the zeolite KL the Pt/KL samples obtained were then calcined under different conditions in order to see the effect of calcination temperature, calcination medium, and calcination time on the dispersion of the platinum. After obtaining the optimum calcination conditions, a set of samples were then prepared under these calcination conditions and used to investigate the different reduction parameters. It was important to observe the effect of varying the different reduction parameters on the dispersion of the platinum. The parameters investigated during reduction were the reduction medium, the reduction temperature and the reduction time.